Особенности характера у инвалидов по зрению и их связь с речевым поведением - Анатон Борисович Дороднев; Николай Альбертович Алмаев (Психология. Журнал Высшей школы экономики, 2011)
The research is aimed at investigation of adaptation to a trauma in visually impaired people and revealing of structure of their temperament and character. The connections between the character and the units of speech of the blind are revealed. For the sample of visually impaired people anxiety with a sharp reaction towards social disapproval and a compensatory keen sense of unity with the universe, nature and people are typical. For all those visually impaired subjects that are involved in the process of overcoming their trauma, it is typical to mention the trauma in their stories. High scores on C.R. Cloninger’s «Self-Forgetfulness» scale reflect the action of compensatory mechanism which helps them to deal with painful experience induced by the loss of sight. The blind who do not mention their trauma in their stories have already passed through the adaptation process and dealt with the stress caused by the loss of sight.